Hot-hole-induced dielectric breakdown in LDMOS transistors. - Labate, L. (IEEE Transactions on electron devices)
A novel failure mechanism in an n-channel lateral double-diffused metal-oxide-semiconductor (LDMOS) transistor biased in the saturation mode is investigated. A correlation between time-to-breakdown and hot hole gate current is established and the static safe operating area (SOA), limited by hot-hole-induced dielectric breakdown, is defined. A method based on the evaluation of the time integral of an "effective" hot-hole gate current is proposed which allows us to estimate the time-to-fail of the device operating in any dynamic (periodic) mode, beyond its static SOA. The prebreakdown degradation of some electrical parameters, attributed to hot hole injection into the gate oxide, is also discussed.